Determination of Biochemical Activities of Aromatic Cyclic Phosphatans in the Culture of Saccharomyces cerevisiae L. - Ozsahin, Ayse Dilek; Erdogdu, Ayse; Kirecci, Oguz Ayhan; Yilmaz, Okkes (Kahramanmaras Sutcu Imam Univ Rektorlugu, 2022)
In this study; the effect of newly synthesized different aromatic cyclic phosphazenes on total protein, glutathione S-transferase (GST) and unsaturated fatty acids in S. cerevisiae culture medium was determined. The experimental groups were organized as control group, and phosphazen molecules groups, then, 20 mu g of phosphazen was added to other cultures, except for the control group of S. cerevisiae culture. All treatments were incubated for 72 hours at 30 degrees C. At the end of incubation, cell pellets were separated and Tris-ETDA buffer was homogenized. Total protein levels were determined from Glutathione S-Transferase (GST) from homogenized. The fatty acid was analyzed from the homogenate obtained with the hexane/isopropanol mixture. According to the results of the experiment, while the total protein values and GST values increased in parallel in the yeast cells to which the phosphazene molecule was added, a decrease in the GST level was found in some groups although the protein amount was increased. It was observed that high levels of oleic acid and palmitoleic acids were among the unsaturated fatty acids in the S. cerevisiae fatty acid composition. It was observed that phosphazenes had both a decreasing and increasing effect on the fatty acid synthesis compared to the molecular groups. It can be concluded that newly synthesized phosphosene molecules have different effects on biochemical parameters in S. cerevisiae. It was thought that this different effect occurs due to the difference in the molecular structure of the phosphocenes.
Keywords: Fatty acid; GlutathioneS-Transferase; Phosphazene molecules; S. cerevisiae; Total protein